2013
DOI: 10.1016/j.juro.2012.09.075
|View full text |Cite
|
Sign up to set email alerts
|

Cryoablation Versus Minimally Invasive Partial Nephrectomy for Small Renal Masses in the Solitary Kidney: Impact of Approach on Functional Outcomes

Abstract: In patients with solitary kidneys, renal cryoablation is associated with superior perioperative outcomes compared to partial nephrectomy. Specifically, partial nephrectomy is not associated with greater loss of renal function than renal cryoablation regardless of the extent of tumor complexity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…For the less complex tumors (R.E.N.A.L. score [4][5][6][7][8], we have demonstrated that the RAPN and OPN are comparable. There was no difference in terms of complications, PSM, and overall functional outcome between the two surgical techniques.…”
Section: Surgical Techniquementioning
confidence: 64%
See 3 more Smart Citations
“…For the less complex tumors (R.E.N.A.L. score [4][5][6][7][8], we have demonstrated that the RAPN and OPN are comparable. There was no difference in terms of complications, PSM, and overall functional outcome between the two surgical techniques.…”
Section: Surgical Techniquementioning
confidence: 64%
“…score [4][5][6][7][8] A total of 63 patients (30 RAPN and 33 OPN) had a R.E.N.A.L. score of 4-8 (Table 3).…”
Section: Surgical Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…This was confirmed in single kidney populations with RF (30) and CA (31). Some authors showed a 100% cancer-free survival for a median follow-up of 46 months for CA (32) with excellent renal function outcomes (33)(34)(35). A few series comparing RF ablation to CA did not show significant differences in oncological and functional outcomes (36,37).…”
Section: Discussionmentioning
confidence: 86%